A unified approach to sensitivity and specificity evaluation of novel potential fluorescent dye probes for proteins - Okladnoy, Yu.G.; Dyubko, T.S. (Functional Materials, 2005)
The existing evaluation criteria of novel fluorescent dyes proposed as potential fluorescent probes for proteins have been considered and a method has been proposed to unify the approach to the sensitivity and specificity evaluation of a new dye at interaction with a protein. The conditions of the evaluation applicability to the property selection and comparison for novel dyes proposed as potential fluorescent probes are analysed.